Analysis of Competency to Employee Motivation and The Impact to Employee Satisfaction (Study Cases at Beauty Services Company) - Rahman Faisal (Journal of Research in Business, Economics, and Education, 2020)
The purpose of this study to test and analyze the influence of employee competency to employee motivation and the impact to employee satisfaction at beauty service company. The data have collected by questionnaires with a total sample of 63 respondents and using a quantitative descriptive approached. The data analysis used was statistical analysis in the form of path analysis. The results of this study indicate the competency has significant effect to employee motivation and the employee motivation also has significant effect to employee’s satisfaction at beauty service company located in South Jakarta. Based on the hypothesis result that H1 accepted to competency effected to motivation, H0 rejected and H1 for motivation to employee satisfaction accepted and H0 rejected.